ECLAC’s thinking from 2010 to 2018: The focus on structural change for equality MEPI - de Moraes, Isaías Albertin [UNESP]; Caixeta Ibrahim, Hermano [UNESP]; Pereira Morais, Leandro [UNESP] (FapUNIFESP (SciELO), 2020)
The article’s unit of analysis is the United Nations Economic Commission for Latin America and the Caribbean (ECLAC/UN). The purpose is to investigate the current phase of its thinking with a strong focus on equality. The research categorizes ECLAC thought in two distinct phases: First, the State-entrepreneur and historical-structuralism method (1948-1990), and second, the management-State and historical-neostructuralism method (1990-present). The hypothesis is that the ECLAC thought since 2010 has moved away from the Productive Transformation with Equity (TPE) proposition-initially defended by Neo-Structuralism-and is establishing a new conception, namely the Structural Change for Equality (MEPI). The present study chose to adopt as technical procedure a systematic approach through the critical evaluation of bibliographic and documentary data on the subject, especially the documents produced by ECLAC.
O pensamento da CEPAL de 2010 a 2018: O enfoque na mudança estrutural produtiva para igualdade MEPI
Keywords: ECLAC; Economic development; Economic history; Economic policy; Latin America